1999
DOI: 10.1046/j.1365-2958.1999.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane cyclopropane fatty acid content is a major factor in acid resistance of Escherichia coli

Abstract: Cyclopropane fatty acid (CFA) formation is a post‐synthetic modification of the lipid bilayer that occurs as cultures of Escherichia coli and many other bacteria enter stationary phase. We report the first distinct phenotype for this membrane modification; early stationary phase cultures of strains lacking CFA (as a result of a null mutation in the cfa gene) are abnormally sensitive to killing by a rapid shift from neutral pH to pH 3. This sensitivity to acid shock is dependent on CFA itself because resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
276
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(296 citation statements)
references
References 49 publications
20
276
0
Order By: Relevance
“…In E. coli, acetate treatment induces cfa expression (Arnold et al, 2001), and deletion increases acid-stress sensitivity (Chang and Cronan, 1999). In C. acetobutylicum, the cfa gene is differentially upregulated following acetate stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In E. coli, acetate treatment induces cfa expression (Arnold et al, 2001), and deletion increases acid-stress sensitivity (Chang and Cronan, 1999). In C. acetobutylicum, the cfa gene is differentially upregulated following acetate stress.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of solvent and carboxylic acid toxicity/stress have been studied mostly in Gram-negative (Gram À ) organisms and notably in Escherichia coli (Arnold et al, 2001;Chang and Cronan, 1999;Hayashi et al, 2003;Isken and de Bont, 1998;Kirkpatrick et al, 2001;Roe et al, 2002;Russell and Diez-Gonzalez, 1998;Sardessai and Bhosle, 2002;Zaldivar and Ingram, 1999). For example, Gram À organisms have evolved adaptive mechanisms to tolerate solvents, including alterations in cell membrane, active secretion, and activation of general stress response (Isken and de Bont, 1998;Sardessai and Bhosle, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase in cyclopropane fatty acid production during [C 2 mim]Cl exposure demonstrates the distinct effect of ionic liquid on the bacterium. A number of studies using E. coli and lactobacilli have demonstrated that methylation of the cis-acyl chain double bond to form a cyclopropane ring plays a significant role in tolerance to acid, salt, butanol, and other stressors by reducing membrane fluidity and decreasing permeability (50)(51)(52)(53)(54). It is probable that cyclopropane fatty acid production plays a similar role in [C 2 mim]Cl tolerance by stabilizing the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…While the biological roles of CFAs in bacteria are not completely understood (Cronan, 2002), it has been demonstrated that cyclopropane-containing lipids protect bacteria from adverse conditions such as acidity (Ballen et al, 1998;Brown et al, 1997;Chang & Cronan, 1999;Kim et al, 2005), freeze-drying (Munoz-Rojas et al, 2006), desiccation (Boumahdi et al, 2001) and exposure to pollutants (Fang et al, 2007;Mrozik et al, 2005Mrozik et al, , 2006. There is some debate as to whether an increase in cyclopropane content of bacterial membranes leads to a decrease in membrane fluidity (Loffhagen et al, 2007;Munoz-Rojas et al, 2006).…”
Section: Introductionmentioning
confidence: 99%